(untitled) (Journal of the College of Education for Women, 2019)
Zora Neale Hurston’s (1891-1960) is an outstanding African Americannovelist, playwright, autobiographer and essayists. Her work is considered as animportant part of the African American and Harlem Literature.**** It represents amilestone and a keystone in the African-American literary canon because it breaksfrom the style of the previous works and makes a beginning of a new style. Hurstonshifts from the black works that stick to racial themes and sheds the light on newaspects and themes in blacks’ life especially on feminist themes. Her exceptional fameculminates in her novel Their Eyes Were Watching God (1937). 1Their Eyes Were Watching God examines with a great deal of artistrythe struggle of a black woman named Janie Crawford to escape the fetters of thetraditional concept about love and marriage and the narrow social restrictions of herclass and sex. She neglects others’ judgment on her and is brave enough to strive forher dream.2The paper concentrates on this novel to show the concept of love and marriagethrough the story of Janie’s Crawford, the novel’s protagonist. In Janie’s plighttowards liberty and recognition, love and happiness, Hurston reflects the coloredwomen’s thrives and experiences in the American black society. Janie, who has theconcept that marriage must involve love and happiness, goes for a search ofunconditional and fulfilling love which she finally finds with her third husband TeaCake, but only after she has passed through the wasteland of being a possessionbefore entering the pear tree garden of her actualized dreams of love and happiness.